The Dialectical Spirals of the Civilization Paradigm - Muh Wasith Achadi (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
The existence of a civilization is of concern to both Western and Eastern scientists. Scientists observe and examine the various factors that led to the fall and rise of a civilization. They also explore various things that make the existence of a civilization survive amidst various challenges. In the perspective of Muslim scientists, there are various factors that cause a civilization to exist and a civilization to collapse. According to them, one of the factors that can cause the collapse of a civilization is tyranny. Meanwhile, one of the most dominant factors determining the existence of a civilization is social justice. This article will elaborate the dialectical spiral civilization paradigm from the perspective of Muslim scientists. Keberadaan peradaban menjadi perhatian para ilmuwan Barat dan Timur. Ilmuwan mengamati dan meneliti berbagai faktor yang menyebabkan jatuhnya suatu peradaban. Mereka juga mengeksplorasi berbagai hal yang membuat eksistensi suatu peradaban tetap bertahan di tengah berbagai tantangan. Dalam perspektif ilmuwan Muslim, ada berbagai faktor yang menyebabkan munculnya peradaban dan kehancuran peradaban. Menurut mereka, salah satu faktor penyebab runtuhnya suatu peradaban adalah tirani. Sedangkan salah satu faktor yang paling dominan menentukan keberadaan suatu peradaban adalah keadilan sosial. Artikel ini akan menguraikan paradigma peradaban spiral dialektis dari perspektif ilmuwan Muslim.